Analisis Relevansi Mata Kuliah Keprodian Dengan Kebutuhan Dunia Kerja Bagi Lulusan Program Studi KPI IAIN Parepare - j, juswanda; Mifdah Hilmiyah (Communication and Islamic Broadcasting Studies IAIN Parepare, 2024)
This research aims to examine the level of relevance of study program courses to the needs of the world of work for graduates of the KPI IAIN Parepare study program. The method used in this research is a quantitative method. Data collection was carried out by distributing questionnaires and documentation. The data analysis technique uses quantitative correlation methods. The KPI study program has 43 study program courses and 16 institute courses, including 32 courses that form knowledge competencies, all courses in the study program are expected to be able to form attitudes and 31 courses that form general skills competencies and 6 courses that form specific skills competencies. The results of the research show that the study program courses and the needs of the world of work for KPI IAIN Parepare graduates are related. This is proven by the results of the Pearson correlation test, which obtained a Pearson correlation value of 0.250, which is at the level of a weak relationship between study program subjects and the needs of the world of work of graduates and has a positive value. Keywords: Competencies, Study Program Courses, Needs of the World of Work, Graduates